Metabolie epidermal necrosis (hepatocutaneous syndrome) in the dog: A clinical and pathological review of 6 spontaneous cases - KOUTINAS (X.K. ΚΟΥΤΙΝΑΣ), C. K.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ), M. N.; KALDRYMIDOU (Ε. ΚΑΛΔΡΥΜΙΔΟΥ), H.; ROUBIES (Ν. ΡΟΥΜΠΙΕΣ), N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Metabolic epidermal necrosis was diagnosed in 6 dogs admitted to the Clinic of Companion Animal Medicine, Faculty of Veterinary Medicine, A.U.T., between 1989 and 1998. Four of these animals were males and 2 females with an age range of 8 to 11.5 years. Bilaterally symmetrical (5/6) or asymmetrical (1/6) skin lesions characterized by alopecia – hypotrichosis (5/6), erythema (6/6), depigmentation (3/6), epidermal colarettes (3/6), ulcers and erosions (6/6), crusts (6/6), footpad and nose hyperkeratosis (5/6), edema (4/6), exudation (3/6), pustules (2/6), scales (2/6) and papules (1/6) were observed in all of the dogs. These lesions were located on the limbs (6/6), the external genitalia (5/6), ventral abdomen (4/6), mucocutaneos junctions (4/6), pressure points (3/6), distal extremities (3/6), nasal philthrum (3/6), muzzle (2/6), axillae (1/6) and on the dorsal aspect of the body trunk (1/6). The most important clinicopathologic findings included anemia (5/6), leucocytosis (3/6), thrombocytopenia (1/6), hypoalbuminaemia (4/5), hyperglycemia (3/6), increased alkaline phosphatase (4/6) and alanino-aminotransferase (5/6) activities, hypocalcaemia (2/5), proteinuria (1/6) and glycosuria (3/6). Liver histopathology, carried out in 4 dogs, revealed vacuolar hepatopathy in all of them. The same underlying disease was suspected in one additional case, whereas pancreatic glucagonoma was a possibility for the remaining dog. Systemic an/or topical treatment, that was attempted in 3 dogs, was unrewarding. All the 6 dogs died (3/6) or were euthanized (3/6) 2 to 17 months after the appearance of the skin lesions.